Paediatric cardiopulmonary resuscitation: Knowledge and perceptions of surf lifeguards. (26th June 2018) - Webber, Jonathon; Moran, Kevin; Cumin, David
Abstract : Aim: To conduct a comprehensive analysis of surf lifeguards' real and perceived ability in paediatric cardiopulmonary resuscitation (CPR), knowledge of child resuscitation protocols and technical competency during a simulated CPR scenario. Methods: Surf lifeguards aged 16 years and over were invited to complete a written survey and simulated test of five cycles of single‐rescuer CPR on a paediatric manikin. In accordance with the latest Australia and New Zealand Committee on Resuscitation (ANZCOR) guidelines, practical skills were assessed by trained observers. A manikin fitted with electronic data‐collection capability recorded technical compression and ventilation skills. Results: A total of 244 participants were entered into the study. Most previous CPR training did not include a paediatric component (53%). Lifeguards rated their ability to perform CPR on an adult as 'highly effective' or 'effective' in 56% of responses. Less than a quarter (23%), however, gave this response when compared to a child. Observed CPR skills were mostly compliant with ANZCOR guidelines (80–99%). Manikin data provided a median compression rate of 115.6 min −1, compression depth of 3.7 cm and tidal volume of 220.0 mL. Almost half of ventilations were too little (45%), and around one fifth were too much (22%). Conclusions: Surf lifeguards are less confident in paediatric CPR. The overall performance of observed and technical CPR skills, which were mostly ANZCOR guideline compliant, suggests that performance could be improved if paediatric‐specific training is provided to supplement the adult‐focused methods currently in use. The use of electronic feedback manikins is recommended to address the technical compression and ventilation issues identified in this study.